Functionalizing walnut protein via consecutive purification and ultrasound modification: Self-assembled structure and interfacial properties - Jisong Zhou; Jingjing Wang; Wenjie Xia; Ying Peng; Jing Yang; Weiping Jin; Dengfeng Peng (Ultrasonics Sonochemistry)
The preparation of plant proteins generally involves three independent steps, which is time-consuming. Here, we integrated these three steps into one consecutive process (one-step preparation), which involved alkali extraction, membrane purification, and ultrasound modification. The obtained walnut protein was evaluated in terms of self-assembled structure, interfacial behaviors, and emulsifying properties. Compared with the traditional preparation method, our one-step preparation regulated the aggregation of walnut protein from a dissolved state to a well-organized assembly. When the ultrasound modification was conducted at 10 W/mL for 30 min, the walnut protein (WP-U2) showed the highest surface hydrophobicity (H0 = 36704), the smallest particle size (205 nm), and highest solubility (58.70 %) at pH 7.0. These well-assembled proteins rapidly diffused, anchored, and rearranged at the oil–water interface, resulting in an increase of the interfacial pressure to 19 mN/m. The adsorbed proteins formed a dense and stiff solid-like interfacial film with a storage modulus of 64 mN/m at an amplitude of 5 %. These enhanced interfacial properties endow WP-U2 with superior emulsifying properties (EAI ∼ 12 m2/g, ESI > 150 min) compared to other groups. This study provides a simple and environmentally friendly way to produce functionalized walnut protein, which shows great potential as an effective food emulsifier.